The challenge of the management of adolescents and young adults with soft tissue sarcomas. Issue 7 (1st March 2018) - Ferrari, Andrea; Bleyer, Archie; Patel, Shreyaskumar; Chiaravalli, Stefano; Gasparini, Patrizia; Casanova, Michela
Abstract: Soft tissue sarcomas are relatively frequent in adolescents and young adults and their clinical management may be complex, partly due to tumor associated factors, but also because different approaches have been adopted by pediatric and adult medical oncologists dealing with the same disease. However, times are changing and in the last few years, management has tended to converge towards a common strategy. Continued and increased international collaboration between pediatric and adult sarcoma groups is of critical importance to improve the quality of treatment as well as research programs dedicated to young patients with soft tissue sarcomas.